The electrical energy situation of French islands and focus on the Corsican situation. (May 2019) - Notton, G.; Duchaud, J.L.; Nivet, M.L.; Voyant, C.; Chalvatzis, K.; Fouilloy, A.
Abstract: The present work aims to present the electrical energy situation of several French islands spread over the World. Various aspects are successively studied: repartition of energy means, renewable energy part in the production with a focus on the intermittent renewable sources, legal and financial aspect. The electrical situation of the islands is compared with the French mainland one. The electricity production cost in the islands are presented and the financial features for renewable energy in France are exposed. In a second part, a focus is realized on the Corsica Island situated in the Mediterranean Sea and partially connected to Italy. Successively, the energy mix, the objective of the new energy plan for 2023 and the renewable energy situation, present and future, are presented. Even if the integration of non-programmable renewable energy plants is more complex in small insular networks, the high cost of electricity generation in such territories encourages the introduction of wind and PV systems. The islands are good laboratories for the development of intermittent and stochastic renewable energy systems. Highlights: Several case studies for French islands spread over the planet. Electrical particularities of the not-interconnected territories and recognition of these specificities by the law. Particular situation of Corsican Island. Integration of intermittent renewable sources in small electrical networks.